Nadiem Makarim’s Speech in the Freedom of Learning Series: Critical Discourse Analysis of Social Situations and Ideology - Sutrsino, Adi; Tjahyadi, Indra (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
This research aims to (1) Explain the transitivity system in Nadiem Makarim speech, (2) Explains the ideology reflected in the speech text. The main character's speech at this time is frequent used as topic study in study Language. A number of study cross disciplinary appear along development role And definition The proposed transitivity system Halliday is an analytical tool for analyzing linguistic data that has been used by Fairclough in his theoretical framework of critical discourse analysis. Based on the purpose of describing the transitivity system and Nadiem Makarim's speech ideology, this research can be categorized as descriptive research. Research result shows the six processes used by Nadiem Makarim in representing his experience, viz material processes, mental processes, relational processes, verbal processes, behavioral processes (behavioral), existential processes. The process that is often used by Nadiema Makarim is the material process followed by the relational process and mental processes. In expressing his ideas, Nadiem Makarim uses a lot of material processes as well show in principle that more Good Act than only just speak. Nadeim Makarim delivered his speech on National Teacher's Day in 2019. And then continued with Nadiem Makarim's speech at the 2020 HGN in the midst of the pandemic.